Incidence of Metastatic Renal Cell Carcinoma in Sulaimaniyah Government, Iraq - Hama, Hardi Tariq; Akhaways, Ismaeel Hama Ameen; Arkawazi, Lusan Abdulhameed (Sulaimani Journal for Pure and Applied Sciences, 2022)
Renal cell carcinoma (RCC) has a well-known tendency to metastasize. Kidney Cancer (KC) has some histopathological subtypes; the most common one is clear cell renal cell carcinoma (ccRCC), which can spread to distant organs in the body like the lungs, brain, bone, and lymphatic system. Multiple RCC metastasis can be treated by complete surgical resection of all metastases if the patient is amenable for surgery, in spite that there is another option in the management of (metRCC) like chemotherapy, radiotherapy and immunotherapy. Full metastasectomy was related to a significant extension of median cancer-specific survival. Also, it is important during multiple metastasectomies; the surgical beds have free of tumours. Primary systemic therapy is targeted therapy (TT) that affect the vascular endothelial growth factor pathway, which improves progression-free survival and overall survival. The results of this study demonstrate that the incidence of metastasized RCC was 0.28 in 2017, which increased until in 2018, it became 0.92, which was the first pick. The second pick was in 2019, which was 1.26. After that, the incidence steadily decreased till 2020 and became 0.57 per 100,000 populations. Regarding types of operation and laterality, partial nephrectomy was done for (45%), radical nephrectomy for 52.5% and 2.5% were non operated, and (64.8%) of the primary tumour was right-sided, and 35.2% was left-sided. Regarding male gender 75 (61.5%) and female 47 (38.5%), non-symptomatic patients were 57.4% while 28.7% had flank pain history, 7.4% had gross hematuria, and 4.1% had back pain symptoms. Route of diagnosis only by ultrasound (US) in 86% and least diagnostic tool is magnetic resonance image (MRI) (0.8%). The most frequent (72.7%) histologic subtype was ccRCC. The most frequent site of distant metastasis was a respiratory system which was 9.8%, then 4.9% metastasized to the skeletal system. In contrast, connective tissue, the endocrine system, and the digestive system had the least common site (0.8%), 10.7% had metachronous, and 13.9% had synchronous metastasis, respectively. Regarding risk factors, 83.4% had a smoking history, the mean body mass index (BMI) was 27.3 kg/m2 , and 46.7% had ahypertension history. This study demonstrated the incidence of MetRCC in the Sulaimaniyah government. Finally, we concluded that the incidence of metastatic RCC increases annually, also synchronous metastasis has higher than metachronous metastasis. In contrast, metastatic RCC is more common in males than females, and most cases of RCC are diagnosed incidentally by a noninvasive imaging method, which was US.
Keywords: Metastatic; Carcinoma; hypernephroma